After the war : nation-building from FDR to George W. Bush - Dobbins, James, 1942- (RAND National Security Research Division, 2008)
In recent decades, the United States' overwhelming military superiority has allowed it to 'overawe' or overrun adversaries with comparative ease. However, consolidating victory and preventing a renewal of conflict has usually taken more time, energy, and resources than originally foreseen. Few recent efforts of this sort can be regarded as unqualified successes, and one or two must be accounted as clear failures. Prior RAND research examined the factors that contribute to this success or failure, including the natures of the society being reformed and of the conflict being terminated, as well as the quality and quantity of the military and civil assets of external actors. This volume addresses the manner in which U.S. policy toward postconflict reconstruction has been created and implemented and the effect that these processes have had on mission outcomes. Through the lens of presidential decisionmaking style and administrative structure, from the post-World War II era through the Cold War, post-Cold War era, and current war on terrorism, it is both possible and necessary to reassess how these elements can work in favor of, as well as against, the nation-building goals of the U.S. government and military and those of its coalition partners and allies.